Annotated bird sighting list for Spring 1986 compiled by Steve Dinsmore - Dinsmore, Stephen J.et al (1986)
An annotated list of birds sighted by Steve Dinsmore. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Spring 1986. Epson - sheet feed